2013
DOI: 10.1063/1.4828757
|View full text |Cite
|
Sign up to set email alerts
|

Optimum high temperature strength of two-dimensional nanocomposites

Abstract: High-temperature nanoindentation was used to reveal nano-layer size effects on the hardness of two-dimensional metallic nanocomposites. We report the existence of a critical layer thickness at which strength achieves optimal thermal stability. Transmission electron microscopy and theoretical bicrystal calculations show that this optimum arises due to a transition from thermally activated glide within the layers to dislocation transmission across the layers. We demonstrate experimentally that the atomic-scale p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 30 publications
4
32
0
Order By: Relevance
“…[6][7][8][9] The latter have attracted attention because, in addition to their enhanced thermal stability, they also possess high strength, high hardness, and outstanding radiation damage tolerance. [10][11][12][13] High strength and high thermal stability were reported previously for Cu-Nb nanolaminates fabricated by physical vapour deposition (PVD) and were attributed to the high density of chemically sharp, lowenergy {111}Cujj{110}Nb Kurdjumov-Sachs (K-S) interfaces. 14 As a result of the PVD fabrication, these nanolaminates have an in-plane grain size-to-thickness ratio of 1-1.3 for both Cu and Nb 15 and hence also contain a high density of triple junctions, where grain boundaries and bimetal interfaces meet.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…[6][7][8][9] The latter have attracted attention because, in addition to their enhanced thermal stability, they also possess high strength, high hardness, and outstanding radiation damage tolerance. [10][11][12][13] High strength and high thermal stability were reported previously for Cu-Nb nanolaminates fabricated by physical vapour deposition (PVD) and were attributed to the high density of chemically sharp, lowenergy {111}Cujj{110}Nb Kurdjumov-Sachs (K-S) interfaces. 14 As a result of the PVD fabrication, these nanolaminates have an in-plane grain size-to-thickness ratio of 1-1.3 for both Cu and Nb 15 and hence also contain a high density of triple junctions, where grain boundaries and bimetal interfaces meet.…”
mentioning
confidence: 89%
“…[18][19][20][21] Although studies have shown that these ARB laminates also exhibit extraordinary thermal stability, the underlying mechanism that leads to their eventual breakdown under high temperatures (700 C) has yet to be unveiled. 6,13,22 In contrast to the PVD laminates, the ARB laminates contain single crystal layers with extremely highaspect-ratio grains (over 30) and hence a very low density of triple junctions. 7 Therefore, previously identified thermally induced mechanisms for layered structures, such as grain boundary migration (e.g., the zig-zag locking mechanism found in the PVD foils 15 ), bulk diffusion controlled crystalline defect migration, 23 and the common pinch off at triple junctions, 24 cannot dominate in the unique nanostructure of the ARB Cu-Nb composites.…”
mentioning
confidence: 98%
“…This is in remarkable contrast to cubic-based nanolayered systems produced by the same technique.Thus, critical length scales below which sizedependent or interface-driven mechanisms emerge in the hcp-bcc system, should they exist, must lie below 90 nm.Furthermore, based on the exceptional properties discovered for ARB Cu-Nb systems, [9,56,[71][72][73][74] we envision that the Zr-Nb nanolayered material will exhibit many unusual and interesting properties, potentially far exceeding those of current coarse-grained Zr.This study opens up an innovative route to manufacturing hcp and bcc nanostructured metals as well as a novel material for pioneering hcp/bcc interface and nanoscale hcp research.…”
mentioning
confidence: 99%
“…While several studies have been undertaken to clarify the mechanical behavior of such films at ambient temperature [4][5][6][7][8][9][10][11][12][13][14][15][16], few have investigated the deformation response at elevated temperatures [17][18][19][20][21][22]. These few studies have mostly used the instrumented indentation technique, which despite the ease of testing presents difficulty in direct interpretation of the results due to the complex stress states involved.…”
Section: Introductionmentioning
confidence: 96%